How do face consciousness and public self-consciousness affect consumer decision-making? - Seung-Hee Lee; Jane E. Workman (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Many individual differences affect consumers in the decision-making process (i.e., what to purchase; when to purchase). Face consciousness and public self-consciousness affect when in the fashion life cycle consumers decide to purchase, as well as what to purchase. Both face consciousness and public self-consciousness are concerned with consciousness (i.e., awareness; mindfulness) and both depend on social comparison processes. But the motivation underlying the social comparisons is different: with face consciousness, social comparisons yield appraisals of prestige and social status; with public self-consciousness, social comparisons yield assessments of situational appropriateness. The purpose of this study was to examine links among face consciousness; public self-consciousness; brand prestige; self-expressive brand (inner; social), and fashion leadership. Participants were 221 university students who completed a questionnaire. Descriptive statistics, Cronbach's alpha reliability, and multivariate/univariate analysis of variance (M/ANOVA) were conducted to analyze data. Results showed that face consciousness and public self-consciousness similarly affected ratings of the social self-expressive brand. However, face consciousness (but not public self-consciousness) influenced ratings of brand prestige and inner self-expressive brand. Public self-consciousness (but not face consciousness) influenced fashion leadership. Thus, while face consciousness and public self-consciousness are both concerned with consciousness, they independently influence consumer decision-making in different ways. Theoretical and practical implications are provided.
Keywords: 650; brand prestige; expressive to brands; face consciousness; fashion leadership; public self-consciousness